2011
DOI: 10.1093/gbe/evr076
|View full text |Cite
|
Sign up to set email alerts
|

Selection for Translation Efficiency on Synonymous Polymorphisms in Recent Human Evolution

Abstract: Synonymous mutations are considered to be “silent” as they do not affect protein sequence. However, different silent codons have different translation efficiency (TE), which raises the question to what extent such mutations are really neutral. We perform the first genome-wide study of natural selection operating on TE in recent human evolution, surveying 13,798 synonymous single nucleotide polymorphisms (SNPs) in 1,198 unrelated individuals from 11 populations. We find evidence for both negative and positive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 88 publications
(147 reference statements)
2
41
0
Order By: Relevance
“…onstrated the functional outcomes of synonymous mutations (Plotkin and Kudla 2011;Waldman et al 2011). Tabulation of cloned rice QTLs, which often have larger effects in the respective populations than the TASs identified in the current study, also indicated the importance of expression differences (Miura et al 2011).…”
Section: Distribution Of Maize Tass and Candidate Genesmentioning
confidence: 52%
“…onstrated the functional outcomes of synonymous mutations (Plotkin and Kudla 2011;Waldman et al 2011). Tabulation of cloned rice QTLs, which often have larger effects in the respective populations than the TASs identified in the current study, also indicated the importance of expression differences (Miura et al 2011).…”
Section: Distribution Of Maize Tass and Candidate Genesmentioning
confidence: 52%
“…Because the rs16998248 T>A polymorphism encodes a synonymous amino acid change (A342A), there is no direct effect on the protein sequence; however, this change can nonetheless modify the expression level of the gene because of the impaired translation efficiency ascribed to different tRNA pools corresponding to alternative codons coding for the same amino acid (Waldman et al, 2011). Therefore, this polymorphism may alter the ZNF217 protein elongation rate based on differences in tRNA pools, leading to decreased expression of ZNF217 and further compromising the formation of protein complexes in which ZNF217 functions as a transcriptional regulator (Carmi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon has been termed codon usage bias (CUB), and many studies support a role of natural selection in this phenomenon (Shields et al 1988; Moriyama and Hartl 1993; Akashi et al 1998; Comeron and Kreitman 1998; Chamary et al 2006; Plotkin and Kudla 2011; Waldman et al 2011; Behura et al 2013; Kober and Pogson 2013). Proposed mechanisms influencing CUB include translational efficiency (Grantham et al 1981; Ikemura 1985; Bulmer 1991; Carlini and Stephan 2003; Rocha 2004; Stoletzki and Eyre-Walker 2007; Parmley and Huynen 2009; Hense 2010; Ran and Higgs 2010, 2012; Sharp et al 2010; Behura and Severson 2011; Shah and Gilchrist 2011; Qian et al 2012; Agashe et al 2013; Lawrie et al 2013; Michely 2013), mRNA stability or folding (Moriyama and Powell 1998; dos Reis et al 2004; Chamary and Hurst 2005; Chamary et al 2006; Novoa and Ribas de Pouplana 2012; Kober and Pogson 2013; Shabalina et al 2013), transcription factor binding (Stergachis 2013), overlap with other functional elements in the genome (Lin 2011), and/or a trade-off between rapid versus accurate translation (Yang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have demonstrated that weak selection shapes patterns of CUB across mammals, including humans, the mammal with the smallest known historical N e (Urrutia and Hurst 2003; Comeron 2004; Lu and Wu 2005; Kondrashov et al 2006; Yang and Nielsen 2008; Waldman et al 2011; Doherty and McInerney 2013), but see (Urrutia and Hurst 2001; Duret 2002). However, theoretical and empirical studies suggest that selective coefficients may not be homogeneous across species.…”
Section: Introductionmentioning
confidence: 99%